Internationales migrations and development in Africa - (:unkn) unknown (My University, 2024)
The main objective of this research is to analyse the effects of international migration on the development of African economies. Through three empirical essays, constituting the three chapters of the thesis, we propose an additional view of the economic implications of international migration in Africa. The analysis of the economic impact of international migration has been limited to three dimensions of development, such as financial inclusion, economic growth and labor market outcomes. Firstly, based on a macroeconomic approach, in the first essay, we analyze the impact of emigration on the dynamics of financial inclusion, using panel data from 32 sub-Saharan African countries. The results highlight a positive and significant impact of emigrant remittances on the eight dimensions of financial inclusion studied. The magnitude of the impact is more strong when it comes to financial inclusion indicators measured at the level of microfinance institutions. Then, in the second essay, we estimate the impact of emigration and immigration flows on economic growth in African countries. The aim is to analyze the effect of migration movements on the economy of a country considered both as a country of origin and destination, as is the case for most African countries. The results show that, on the one hand, emigration has a negative impact on total factors productivity. On the other hand, immigration has a positive impact on total factors productivity of host countries through the human capital they bring with them. Finally, in the third essay, we carry out a complementary study using a microeconomic approach. This study aims to estimate the effect of immigrant workers on competing natives's labor market outcomes in Togo. The results show that, the increase in immigrants workers have a negative impact on the employment and wages of competing natives.
Keywords: African Research